Distance to trauma centres among gunshot wound victims: identifying trauma 'deserts' and 'oases' in Detroit. (3rd June 2019) - Circo, Giovanni M
Abstract : Introduction: Among the factors related to survival among individuals with gun shot wounds (GSW) is distance to trauma care. Relatively little is known about neighbourhood-level patterns of GSW mortality and distance to hospitals with trauma centres. This study focuses on distance to the nearest trauma centre as a correlate of survival among GSW victims. Methods: Fatal and non-fatal shooting incident data for 9, 205 victimisation in Detroit, Michigan between 2011 and 2017 were collected. A Bayesian conditional autoregressive model was utilised to estimate block-group levels of GSW mortality. Clustering techniques were used to identify spatially proximate neighbourhoods with higher or lower than expected rates of GSW mortality. Results: Distance to the nearest trauma centre was associated with a 22% increase in fatal outcomes, per-mile (OR 1.22, 95% CI, 1.06 to 1.40) after adjusting for block-group level covariates. A Getis-Ord Gi * analysis identified 91 block groups with lower than expected rates of GSW mortality and 12 block-groups with higher than expected rates. Conclusion: Distance to the nearest trauma centre is associated with GSW victim survival. Clusters of block-groups with below-average GSW mortality were observed within close proximity of major trauma centres in Detroit. Improving speed and access to trauma care may play a role in reducing GSW mortality.